(untitled) (Innovative professional education, 2024)
In the article, the author highlights the diagnosis of readiness of future qualified workers for independent work in conditions of mixed training. It notes the difficulties that students of education face when performing independent work in the conditions of mixed education. Reveals the content of technical, psychological and professional readiness in the structure of the method of organizing the independent work of future skilled workers in the conditions of mixed training and its essence, the impact of diagnosis on the quality of the organization of independent work and their performance by future skilled workers.